Growth and Nutrient Uptake of Organic Basmati Rice (Oryza sativa L.) as Influenced by Diversified Nutrient Sources - Critykar, Jungjit; Shivay, Y. S.; Kumar, Dinesh; Prasanna, Radha (International Journal of Bio-resource and Stress Management, 2026)
A field experiment was conducted during the kharif (May–November, 2016) at ICAR-Indian Agricultural Research Institute, New Delhi, India to assess the growth response and nutrient uptake of organic Basmati rice (Oryza sativa L.) as influenced by diversified nutrient sources under a long-term field experiment. This long-term organic farming of the Basmati rice-wheat cropping system experiment was initiated in the year of 2003 and continued till 2016 with the same layout and treatments. Sixteen treatments comprising combinations of farmyard manure (FYM), green manures (Sesbania green manure, SGM, and Leucaena green leaf manuring, LGLM), blue-green algae (BGA), and Azotobacter were evaluated in a randomized block design with three replications. The combined application to both rice and wheat (T16: SGM+FYM+BGA to rice and LGLM+FYM+Azotobacter to wheat) significantly improved plant height (112.6 cm), tiller number (568.5 m-2), leaf area index (6.15), and dry matter accumulation (1350.3 g m-2 at 90 DAT). Application of T16 also recorded the highest uptake of N (125.3 kg ha-1), P (16.4 kg ha-1), and K (169.5 kg ha-1), along with Fe (4,873.8 g ha-1), Zn (1,902.3 g ha-1), Mn (1,455.9 g ha-1), and Cu (847.4 g ha-1). The results highlighted that the integrated application of organic inputs enhanced growth, yield attributes, and nutrient uptake in organic Basmati rice cultivation. Our findings underscore the sustainable cultivation of organic Basmati rice with the application of diversified organic nutrient sources.